2008
DOI: 10.1002/prot.21864
|View full text |Cite
|
Sign up to set email alerts
|

pH sensitivity of type III secretion system tip proteins

Abstract: Many pathogenic gram-negative bacteria employ type III secretion systems to transport proteins into the host cell membrane and cytoplasm to subvert normal cellular functions. The type III secretion apparatus consists of a basal body spanning the inner and outer bacterial membranes and a needle which extends away from the bacterium. Recent work has found that a special class of proteins localizes to the tip of the needle to control secretion of effector proteins. Five of these tip proteins are IpaD (Shigella fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Alternatively, the tip complex could also serve as a sensor of the external pH. In this context, it is interesting that the tip complex protein SipD undergoes a conformational change at pH 5 to 6 (346). It remains to be investigated whether pH sensing is also involved in the control of effector protein secretion in other animal-pathogenic bacteria.…”
Section: Control Of Effector Protein Translocation By Ph Sensing and mentioning
confidence: 99%
“…Alternatively, the tip complex could also serve as a sensor of the external pH. In this context, it is interesting that the tip complex protein SipD undergoes a conformational change at pH 5 to 6 (346). It remains to be investigated whether pH sensing is also involved in the control of effector protein secretion in other animal-pathogenic bacteria.…”
Section: Control Of Effector Protein Translocation By Ph Sensing and mentioning
confidence: 99%
“…Far-UV CD, intrinsic fluorescence and static light scattering data were collected and analyzed as previously described. 7 The thermal stability data acquired using spectroscopy techniques was incorporated into EPDs using Matlab software package (The Mathworks, Natick, MA). Details of EPD construction have been discussed previously.…”
Section: Preparation Of Recombinant Proteins and Biophysical Methodsmentioning
confidence: 99%
“…6 IpaD is an easily purified, stable protein that we have previously studied by biophysical analysis. 7 IpaB, however, is more complex. Purification of large quantities of IpaB in E. coli requires coexpression with its cognate chaperone, IpgC, forming a heterodimer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work indicated that all of the putative antigens aggregated significantly at pH 5 and 6 at elevated temperatures. 34 This physical degradation pathway was selected because it could be easily adapted for high throughput screening and reflects a major pathway for the alteration and loss of activity of many proteins. 34 An assay was developed employing 96-well plates at 558C using a SpectraMax plate reader (Molecular Devices, Sunnyvale, CA) which measured the time-dependent optical density increase at 360 nm.…”
Section: Excipient Screeningmentioning
confidence: 99%
“…A 10 mM histidine/5 mM phosphate buffer was selected since this buffer was the initial choice for final formulation based on earlier studies. 34 Although the zero-point charge of the aluminum hydroxide adjuvant in the phosphatecontaining buffer was not measured, it is expected that this buffer still has a zero-point charge that produces electrostatic interaction with the antigen. The concentration of the proteins prior to adjuvant addition was confirmed with an Agilent 8453 diode array spectrophotometer by measuring ultraviolet (UV) absorption spectra from 200 to 400 nm.…”
Section: Adjuvant-binding Studiesmentioning
confidence: 99%